Corrective Action Analysis of GMP Implementation in the Fried Shallot Agroindustry (Case Study at CV Dua Putri Sholehah) - Dhuha, Ahmad; Taufik Setyadi, Taufik Setyadi; Risqi Firdaus Setiawan, Risqi Firdaus Setiawan (Jurnal Bisnis dan Manajemen, 2025)
This study examines the root causes of failures in the implementation of Good Manufacturing Practices (GMP) in small and medium-sized enterprises (SMEs), with a focus on human resource factors and employee work behavior. Although GMP implementation has been widely studied, research that positions behavioral aspects as the primary root cause of GMP non-compliance at the SME level remains limited. This study aims to analyze corrective actions based on the root causes of GMP non-compliance that do not meet established standards. The study employs a qualitative analysis method using interview and questionnaire approaches, with data analyzed using NVivo version 12 Pro software. The assessment of GMP implementation at CV Dua Putri Sholehah was conducted based on eleven aspects and involved ten informants from the production, packaging, and peeling sections. The results indicate that employee health and hygiene are the most problematic aspects, particularly low compliance with the use of Personal Protective Equipment (PPE). Root cause analysis reveals that failures in GMP implementation are more dominantly influenced by employee behavioral factors related to weak internal regulations and supervision systems rather than limitations in physical facilities. These findings provide a new perspective in the food safety literature by emphasizing that successful GMP implementation in SMEs is highly dependent on the management of employee behavior and compliance. The recommended corrective actions include optimizing regulations and supervision through the improvement of Standard Operating Procedures (SOPs), strengthening supervision systems, consistent enforcement of sanctions, increasing GMP socialization and education, and conducting regular audits and evaluations.